Analisis Determinan Ketimpangan Pendapatan dalam Kerangka Pilar Pembangunan Berkelanjutan (SDGs) di Provinsi Riau - Herman Herman; Putra Budi Ansori (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This paper examines the determinants of income inequality within the SDGs framework in Riau Province. Utilizing BPS secondary data from 2018–2025 across 12 regencies/cities, data were estimated using te random effect modelapproach applied to panel regresiion in EViews 12. F-test finding indicate that-HDI, LN_GRDP, and our jointly and significant influences on the Gini Ratio (R2 = 39.68%). Partially (t-test), HDI has a significant positive effect due to labor polarization in modern sectors. Conversely, LN_GRDP has a significant negative effect, confirming a trickle-down effect in reducing inequality. Meanwhile, OUR has no significant effect due to high labor absorption in Riau's informal agricultural and plantation sectors.